Antimicrobial screening of crude extracts of Talaromyces purpureogenus strains (Ascomycota) from bee bread of honey bee Apis mellifera - Vočadlová, Kateřina; Justus Liebig University Giessen (My University, 2024)
Shortfalls in the pollination service provided by wild and managed pollinators, such as honey bees Apis mellifera, threaten agricultural production and global food security. Although the use of therapeutics helps to control the Varroa mite infestations, and the pathogen load in A. mellifera colonies, more effective and sustainable strategies are needed to prevent the losses. Honey bees coexist with fungi that colonize hive surfaces and pollen, some of them are opportunistic pathogens, but many are beneficial species that produce antimicrobial compounds for pollen conservation and regulate pathogens. Herein, I describe seven fungal strains of Talaromyces purpureogenus from the bee bread of A. mellifera and investigate the antimicrobial potential of their crude organic extracts against honey bee pathogens under laboratory conditions. First, I added the extracts to a diet of bees infected with the chronic bee paralysis virus (CBPV). Then I tested the in vitro activity of the extracts against Paenibacillus alvei (associated with European foulbrood disease) and three Aspergillus species that cause stonebrood disease. The antiviral effect was further determined in mammalian cell lines against feline calicivirus (FCV), feline coronavirus (FCoV), and influenza viruses. Three extracts (from strains B13, B18, and B30) mitigated CBPV infection and improved the survival rate of bees, whereas other extracts had no effect (B11 and B49) or were harmful (B69 and B195). In the mammalian cell lines, extract B18 inhibited the replication of FCV and FCoV in mammalian cells and reduced the infectivity of FCoV by ~99%. The extract B195 also reduced the FCoV infectivity (by ~90%) but caused cytotoxicity at higher concentrations, which could explain the negative effect on honey bee survival rate. The protective effect of the extracts B18 and B195 (at non-toxic concentrations) was also observed against influenza A viruses. In the antibacterial assay, the extracts B18 and B195 inhibited the growth of P. alvei at a concentration of 0.39 mg/mL. Bioactivity-guided dereplication revealed that the activity correlated with the presence of diketopiperazines, a siderophore, and three unknown compounds. The results indicate that the compounds obtained by fermentation from T. purpureogenus extracts from are suitable as prophylactic or therapeutic feed additives to promote the resistance of honey bees to viral and bacterial pathogens. Furthermore, I propose that non-pathogenic fungi such as Talaromyces spp. and their metabolites in bee bread are an unexplored source of compounds that could be an important prerequisite for disease prevention. Agricultural practices that involve the application of fungicides can disrupt the fungal community and therefore negatively impact the health of bee colonies.
Keywords: Honey bee; Apis mellifera; Talaromyces; Natural products; Antiviral activity; Antimicrobial activity; Fungal extracts; Fungal compounds; ddc:500; ddc:570; ddc:630